2021
DOI: 10.1192/bjo.2021.977
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of quarantine on mental health: insights from the COVID-19 international border surveillance study in Canada

Abstract: Background Nations throughout the world are imposing mandatory quarantine on those entering the country. Although such measures may be effective in reducing the importation of COVID-19, the mental health implications remain unclear. Aims This study sought to assess mental well-being and factors associated with changes in mental health in individuals subject to mandatory quarantine following travel. Method Travellers arriving at a large, urban international airport compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The study found workers who had faced travel quarantines had poor mental wellbeing than those who had not faced travel quarantines. Consistent with the findings of studies from other populations elsewhere where individuals facing travel quarantines were associated increased risk of depression, anxiety, stress [27], suicidal ideation and selfharm [58], and decline mental health well-being [59]. Furthermore, experiencing common COVID-19 related symptoms was associated with poor mental well-being.…”
Section: Discussionsupporting
confidence: 85%
“…The study found workers who had faced travel quarantines had poor mental wellbeing than those who had not faced travel quarantines. Consistent with the findings of studies from other populations elsewhere where individuals facing travel quarantines were associated increased risk of depression, anxiety, stress [27], suicidal ideation and selfharm [58], and decline mental health well-being [59]. Furthermore, experiencing common COVID-19 related symptoms was associated with poor mental well-being.…”
Section: Discussionsupporting
confidence: 85%
“…The mental health of COVID-19 patients declines significantly during self-quarantine, with adolescents being affected to a greater degree than adults. 33 In particular, adolescents are more concerned with the government’s infection-control measures than COVID-19 itself, which increases their levels of anxiety and depression, and decreases their satisfaction with life. 34 Therefore, even asymptomatic or mildly symptomatic COVID-19 adolescent patients should be considered high-risk groups and provided with accurate information to prevent negative social and emotional consequences of infection control measures.…”
Section: Discussionmentioning
confidence: 99%
“… 6 - 8 , 26 Canadian researchers found that most SARS survivors experienced good physical recovery from their illness; however, 33% reported a significant decrease in mental health 1 year later. 27 A follow-up study of SARS survivors reported that 40% of patients continued to experience chronic fatigue for a mean of 41 months after SARS. Female SARS survivors exhibited higher stress levels and higher levels of depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%